Biodegradable inkjet-printed electrochromic display for sustainable short-lifecycle electronics. Issue 47 (10th November 2020) - Pietsch, Manuel; Schlisske, Stefan; Held, Martin; Strobel, Noah; Wieczorek, Alexander; Hernandez-Sosa, Gerardo
Abstract : We report on inkjet-printed, wearable electrochromic displays with certified biodegradability according to the international standard 14855 for short-lifecycle applications. Abstract : The fabrication of electronics on the basis of biofriendly materials aims to counterbalance the negative trends conveyed by the short life-cycle of electronics. Furthermore, these materials open the possibility to develop optoelectronic technologies which will be in contact with the human body. In this work, we present an electrochromic display fabricated by resource- and energy-efficient digital printing techniques. The biodegradation of the device is certified under the ISO 14855 standard. The display comprises of a poly(3, 4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) electrochromic layer, a gelatin-based electrolyte and Au electrodes deposited on a cellulose di-acetate substrate. We investigate the impact of various naturally sourced ionic species on the ionic conductivity of the electrolyte and the figures of merit of the display. The printed devices show an electrochromic contrast of 32 ± 4% and switching times of 3.0 ± 1.4 s, comparable to the spincoated reference devices. The utilization of inkjet printing enables the fabrication of different device designs with individually addressable pixels. The display can be worn innocuously on the skin without loss of performance thanks to the self-adhesion properties of the gelatin hydrogel. The present work highlights the use of industrial relevant technology for the fabrication of truly ecofriendly optoelectronic systems.